Acute Effects of Continuous and Intermittent Blood Flow Restriction on Movement Velocity During Bench Press Exercise Against Different Loads - Wilk, Michal; Gepfert, Mariola; Krzysztofik, Michal; Stastny, Petr; Zajac, Adam; Bogdanis, Gregory C. (Frontiers in Physiology, 2020)
Abstract: This study evaluated the effects of continuous and intermittent blood flow restriction (BFR) with 70% of full arterial occlusion pressure on bar velocity during the bench press exercise against a wide range of resistive loads. Eleven strength-trained males (age: 23.5 ± 1.4 years; resistance training experience: 2.8 ± 0.8 years, maximal bench press strength - 1RM = 101.8 ± 13.9 kg; body mass = 79.8 ± 10.4 kg), performed three different testing protocols in random and counterbalanced order: without BFR (NO-BFR); intermittent BFR (I-BFR) and continuous BFR (C-BFR). During each experimental session, subjects performed eight sets of two repetitions each, with increasing loads from 20% to 90% 1RM (10% steps), and 3 min rest between each set. In the C-BFR condition occlusion was kept throughout the trial, while in the I-BFR, occlusion was released during each 3 min rest interval. Peak bar velocity during the bench press exercise was higher by 12-17% in both I-BFR and C-BFR compared with NO-BFR only at the loads of 20%, 30%, 40%, 50% 1RM (p < 0.001), while performance at higher loads remained unchanged. Mean bar velocity was unaffected by occlusion (p = 0.342). These results indicate that BFR during bench press exercise increases peak bar velocity and this may be used as an enhanced stimulus during explosive resistance training. At higher workloads, bench press performance was not negatively affected by BFR, indicating that the benefits of exercise under occlusion can be obtained while explosive performance is not impaired.